PEMANFAATAN MEDIA VISUAL DALAM TERCAPAINYA TUJUAN PEMBELAJARAN - Cecep Kustandi; Muhammad Farhan; Asfara Zianadezdha; Azahra Kurnia Fitri; Nabilla Agustia L (Akademika : Jurnal Teknologi Pendidikan, 2021)
Media is needed in the learning process because learning activities are a process of conveying information between sources(teacher) and recipients (students). This study was conducted to analyze the use of visual media as an effort to achieve learning objectives. The library research method is used to collected data and information contained in the library room related to the use of media and learning objectives. Data was collected by identifying articles, books, and other supporting documents which were then analyzed. The result of this study shows that using visual media in the learning process can help students to develop visual skills. In addition, visual media is a learning tool that can develop students' imagination in learning activities.Thus, this study describes the use of visual media as learning media that can help students improve their mastery of events that are impossible to present in the classroom